Comparison of metal stents versus plastic stents for preoperative biliary drainage: a meta‐analysis of five randomized controlled trials. Issue 7 (27th April 2021) - Zhang, Wei; Xu, Lin; Che, Xu
Abstract: Background: Although routine preoperative biliary drainage (PBD) is generally not recommended for patients with malignant distal biliary obstruction (MDBO), it is still necessary in many cases. The objective of this study is to compare the effects of metal stents (MSs) and plastic stents (PSs) on PBD in patients with MDBO. Methods: All the randomized controlled trials (RCTs) that compared MS with PS for PBD and published from the date of database establishment to September 2020 were identified by searching the PubMed, EMBASE and Cochrane databases. Results: Five RCTs involving 445 patients were included. There were 201 cases in the MS group, with 244 in the PS group. Re‐interventions (relative risk (RR) = 0.40, 95% confidence interval (CI) 0.21–0.75, P = 0.004), stent occlusions (RR = 0.36, 95% CI 0.18–0.75, P = 0.006), postoperative complications (RR = 0.76, 95% CI 0.59–0.97, P = 0.03) and preoperative cholangitis (RR = 0.19, 95% CI 0.05–0.78, P = 0.02) were lower in the MS group than in the PS group. Preoperative pancreatitis (RR = 2.11, 95% CI 1.06–4.19, P = 0.03) was higher in the MS group than in the PS group. No significant difference was observed in the overall preoperative complications, postoperative pancreatic fistulas, delayed gastric emptying, wound infections and postoperative bleeding between these two groups. Conclusions: MS and PS exerted a similar effect on PBD, but PS had a higher risk of preoperative stent obstruction and postoperative complications, requiring more frequent interventions preoperatively. However, larger sample and higher quality RCTs are necessary for further verification. Abstract : (i) When malignant distal biliary obstruction needs to perform conventional preoperative biliary drainage, which of the metal stents and plastic stents (PSs) are better, there is still a lack of high‐level evidence, so this article is the first one regarding the meta‐analysis of all existing randomized controlled trials; (ii) This article found that the use of both metal stents and PSs showed a similar effect on preoperative biliary drainage, but PSs had a higher risk of stent obstruction before the operation, thus requiring more frequent interventions before the operation. This is not what was previously found in meta‐analysis.